Use of negative pressure therapy in the management of complex wounds initial experience of 4 years - Barker-Antonio, Alan; Lopez-Martinez, Emmanuel; Hernandez-Cruz, Elias; García-Manzano, Roberto Armando; Dávila-Ruíz, Ediel Osvaldo; Lopez, Clara Lorena Ortiz (International Journal of Research in Medical Sciences, 2021)
Background: Wound management with negative pressure therapy has been used in the treatment of complex wounds in both inpatient and outpatient settings, and is increasingly used in primary care and outpatient management, as it helps to reduce patient days of hospital stay. We describe the initial 4-year experience in the use of negative pressure therapy in the management of complex wounds. Methods: A retrospective, cross-sectional and descriptive study of our experience of the use of negative pressure therapy for the management of complex wounds in 5 years. Results: A total of 89 patients with complex wounds managed with TPN were analysed, of which 53 were men (62.9%) and 33 were women (37.1%). Suprafacial therapy was used in 64 cases (73%). The ABTHERA® system was used in 25 cases (27%). Among the etiology of complex wounds, vulvar abscess was recorded in 1 case (1.1%), firearm wound in 1 case (1.1%), Fournier's gangrene in 1 case (1.1%), septic arthritis in 1 case (1.1%), burn wounds in 1 case (1.1%), septic arthritis in 1 case (1.1%), and burn wounds in 1 case (1.1%). 1%), burn wounds in 5 cases (5.6%), pressure ulcer wound in 6 cases (6.7%), necrotizing fasciitis in 19 cases (21.3%), abdominal sepsis in 26 cases (29.2%), surgical wound infection in 29 cases (32.5%). Conclusions: The use of negative pressure therapy and protocolized management has provided patients in our institution with a viable therapeutic option.